Pengembangan E-Modul Praktikum Bermuatan Etnosains pada Materi Hidrolisis Garam dalam Pembuatan Telur Asin - Ramadhani, Muhammad Agil; Al Idrus, Syarifa Wahidah; Rahmawati, Rahmawati (Lembaga Yasin AlSys, 2025)
This development research aimed to describe the levels of validity and practicality of an ethnoscience-based practicum e-module on salt hydrolysis in salted egg production developed for senior high school students. The study employed a research and development (R&D) method with the 4D model (Define, Design, Development, and Disseminate), involving 33 Grade XI MIA 5 students of SMAN 8 Mataram in the 2024/2025 academic year as trial subjects. The validity of the e-module was assessed by three validators using Aiken’s V index and obtained a value of V = 0.88, indicating that the ethnoscience-based practicum e-module on salt hydrolysis in salted egg production is highly valid and suitable for use. The practicality of the e-module was measured through student response questionnaires and showed positive responses, with an average practicality score of 91% across all evaluated aspects. These findings indicate that the developed ethnoscience-based practicum e-module meets the criteria of validity and practicality and can be used as a supporting medium in the learning process, particularly for salt hydrolysis material.